Limitation of Intraoperative Transcranial Electrical Stimulation-Motor Evoked Potential Monitoring During Brain Tumor Resection Adjacent to the Primary Motor Cortex - Hui Jae Do; Han Gil Seo; Byung-Mo Oh; Chul-Kee Park; Jin Wook Kim; Young Doo Choi; Seung Hak Lee (Annals of Rehabilitation Medicine, 2018)
Transcranial electrical stimulation-motor evoked potential (TES-MEP) is a valuable intraoperative monitoring technique during brain tumor surgery. However, TES can stimulate deep subcortical areas located far from the motor cortex. There is a concern about false-negative results from the use of TES-MEP during resection of those tumors adjacent to the primary motor cortex. Our study reports three cases of TES-MEP monitoring with false-negative results due to deep axonal stimulation during brain tumor resection. Although no significant change in TES-MEP was observed during surgery, study subjects experienced muscle weakness after surgery. Deep axonal stimulation of TES could give false-negative results. Therefore, a combined method of TES-MEP and direct cortical stimulation-motor evoked potential (DCS-MEP) or direct subcortical stimulation should be considered to overcome the limitation of TES-MEP.